Petrology and Geochemistry of Serpentinites Associated with the Ultra-High Pressure Lago di Cignana Unit (Italian Western Alps). (30th May 2019) - Gilio, Mattia; Scambelluri, Marco; Agostini, Samuele; Godard, Marguerite; Peters, Daniel; Pettke, Thomas
Abstract: In the Western Alps, the ophiolitic Zermatt–Saas Zone (ZSZ) and the Lago di Cignana Unit (LCU) record oceanic lithosphere subduction to high (540°C, 2·3GPa) and ultra-high pressure (600°C, 3·2GPa), respectively. The top of the Zermatt–Saas Zone in contact with the Lago di Cignana Unit consists of olivine + Ti-clinohumite-bearing serpentinites (the Cignana serpentinite) hosting olivine + Ti-clinohumite veins and dykelets of olivine + Ti-chondrodite + Ti-clinohumite. The composition of this serpentinite reveals a refertilized oceanic mantle peridotite protolith that became subsequently enriched in fluid-mobile elements (FME) during oceanic serpentinization. The olivine + Ti-clinohumite veins in the Cignana serpentinite display Rare Earth Element (REE) and FME compositions quite similar to the host-rock, which suggests closed-system dehydration of this serpentinite during subduction. The Ti-chondrodite-bearing dykelets are richer in REE and FME than the host-rock and the dehydration olivine + Ti-clinohumite veins: their Nd composition points to a mafic protolith, successively overprinted by oceanic metasomatism and by subduction zone recrystallization. These dykelets are comparable in composition to eclogites within the ultra-high pressure LCU that derive from subducted oceanic mafic crust. Different from the LCU, serpentinites from the core domains of the ZSZ display REE compositions indicating a depleted mantle protolith. The oceanic serpentinization of these rocks led to an increase in FME and to seawater-like Sr isotope compositions. The serpentinites sampled at increasing distance from the ultra-high pressure LCU reveal different mantle protoliths, still preserve an oceanic geochemical imprint and contain mafic dykelets affected by oceanic metasomatism. The subduction zone history of these rocks thus occurred under relatively closed system conditions, the only possible change during subduction being an enrichment in As and Sb recorded by the serpentinites closer to the crustal LCU. The ZSZ and Cignana serpentinites thus likely evolved in a slab setting and were weakly exposed to interaction with slab-derived fluids characteristic of plate interface settings. Our data suggest two possible scenarios for the evolution of the studied ZSZ and Cignana serpentinites. They are either part of a coherent ophiolite unit whose initial lithospheric mantle was variably affected by depletion and re-fertilization processes, or they belong to separate tectonic slices derived from two different oceanic mantle sections. In the Cignana serpentinite atop the ZSZ, the presence of Ti-chondrodite dykelets similar in composition to the LCU eclogites suggests these two domains were closely associated in the oceanic lithosphere and shared the same evolution to ultra-high pressure conditions during Alpine subduction.